(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2007)
Goats fed on high quality and valuable forage provide the production of high quality milk and dairy product Improper and poor feeding during lactation period reduce milk yield, weaken animal’s organism, has an influence on breeding and fertility ability and metabolic processes in goats. The goal of our research was to assess the influence of different feed additives on organic goat milk productivity and quality indices. In Latvian local goat feeding of sunflower cake and buckwheat meal increased milk yield by 7,3%, reduced feed units by 3,8% and by 5,2% reduced consumption of digestible protein as well as increased milk fat and protein content in goat milk by 10% and 4,7%> respectively compare to control. Feeding of wheat bran and buckwheat meal increased milk yield by 5,4%>, reduced feed units by 1,5% and by 3,0% reduced consumption of digestible protein as well as increased protein content in goat milk by 3,0% compare to control. Results of milk analysis on milk cells cytology and immunity indices show that feed additives used, and particularly sunflower cake and buckwheat meal, have a beneficial effect on immunity in animal organism.